Effect of silver diamine fluoride combined with photodynamic therapy on primary enamel microhardness - Kiana Valizade; Bahman Seraj; Sara Ghadimi; Mohammad Javad Kharazifard; Nasim Chiniforush (Photodiagnosis and Photodynamic Therapy, 2024)
Objectives: This study aimed to assess the effect of silver diamine fluoride (SDF) combined with photodynamic therapy (PDT) on primary enamel microhardness. Materials and Methods: This in vitro, experimental study was conducted on 40 extracted primary molars with sound buccal/lingual surfaces. The baseline enamel microhardness of the teeth was initially measured by a Vickers hardness tester. Next, the teeth were randomly assigned to four groups (n = 10) for treatment with SDF, PDT, SDF plus PDT, and control (no intervention). After the intervention, the teeth underwent a 14-day pH-cycling, and enamel microhardness was measured again. The change in microhardness was calculated for each group, and comparisons were made by two-way ANOVA and t-test (alpha = 0.05). Results: The mean secondary microhardness of the three intervention groups was significantly higher than that of the control group (P<0.05). Despite slightly higher microhardness in SDF + PDT group, followed by the SDF group, the difference in secondary microhardness was not significant among the three intervention groups (P>0.05). Conclusion: Treatment of primary enamel with SDF or PDT can increase its microhardness and enhance remineralization. However, combined use of SDF and PDT had no additional advantage over the use of SDF alone.